2009
DOI: 10.1080/09593330903029424
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to the anaerobic treatment of municipal wastewater in temperate climates through primary sludge fortification

Abstract: It is proposed that anaerobic treatment of municipal wastewater in temperate climates is attainable through the fortification of wastewater with primary sewage sludge to enhance the chemical oxygen demand (COD). Three bench-scale up-flow anaerobic sludge blanket (UASB) bioreactors (0.5 L) were operated to provide a preliminary verification of this approach. Mass and energy balances were modelled using the GPS-X (COST model, population equivalent of 118,500) to determine the energy balance of the primary sludge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…As a passive process, the technology approaches a zero parasitic electrical energy demand, subsequently affording the opportunity to approach energy neutral wastewater treatment for individual small-scale works and without the demand for sludge imports. However, there is a long-held perception that anaerobic treatment cannot be implemented in a northern European context as the low organic wastewater strength, a facet of combined sewerage, is insufficient to support growth (Alaerts et al, 1993;Lester et al, 2009). In addition, the ambient wastewater temperature is below those trialled to date in AWSP (around 20-25˚C) and is thus below the optimum growth conditions typically cited for anaerobic microbial consortia.…”
Section: Introductionmentioning
confidence: 99%
“…As a passive process, the technology approaches a zero parasitic electrical energy demand, subsequently affording the opportunity to approach energy neutral wastewater treatment for individual small-scale works and without the demand for sludge imports. However, there is a long-held perception that anaerobic treatment cannot be implemented in a northern European context as the low organic wastewater strength, a facet of combined sewerage, is insufficient to support growth (Alaerts et al, 1993;Lester et al, 2009). In addition, the ambient wastewater temperature is below those trialled to date in AWSP (around 20-25˚C) and is thus below the optimum growth conditions typically cited for anaerobic microbial consortia.…”
Section: Introductionmentioning
confidence: 99%
“…In countries with moderate climates, a more holistic approach to the wastewater flowsheet has been developed (Sato et al 2006) by integrating anaerobic pretreatment of the settled wastewater prior to aerobic biological treatment. Advantages of this flowsheet include additional production of biogas from solubilised organics, a reduction in aeration energy demand facilitated by the reduction in organic load and lower biological sludge yields (Lester et al 2009;Sutton et al 2009Sutton et al , 2010. However, the low organic substrate concentration within combined sewers and low domestic wastewater temperatures have been perceived as constraints for widespread implementation of anaerobic wastewater treatment.…”
Section: Introductionmentioning
confidence: 98%
“…However, the low organic substrate concentration within combined sewers and low domestic wastewater temperatures have been perceived as constraints for widespread implementation of anaerobic wastewater treatment. These conditions can reduce the rate of organic biodegradation by anaerobic bacteria, negatively impacting on methane gas production and wastewater effluent quality, and as such may destabilise the anaerobic microbial community (Lester et al 2009). However, several pilot scale studies have now demonstrated effective anaerobic treatment of low strength, low temperature domestic wastewater by utilising reactors that separate hydraulic retention time from solids retention time to improve retention of anaerobic bacteria and increase organic loading (Uemura & Harada 2000) or through manipulation of the flowsheet to increase organic strength of the feedwater (Lester et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) Comparison of energy demands of AeMBRs and AnMBRs, assuming complete retention of solids, suggests that although the latter would have a lower energy demand, the capital cost of the membrane material would be as much as three times higher, as a result of the lower fluxes encountered in anaerobic systems. Zhang et al [55] MLSS: mixed liquid suspended solids; CFV: crossflow velocity; TMP: transmembrane pressure; ∆P: pressure losses; E CF,P : energy required for pumping and to control fouling; E PER : energy required to pump permeate; E TOT : total energy requirements; nr: not recorded.…”
Section: Implications Of the Anaerobic Flow-sheetmentioning
confidence: 99%